RNA Structure Duplications and Flavivirus Host Adaptation - Villordo, Sergio (2016)
Flaviviruses include a highly diverse group of arboviruses with a global distribution and a high human disease burden. Most flaviviruses cycle between insects and vertebrate hosts; thus, they are obligated to use different cellular machinery for their replication and mount different mechanisms to evade specific antiviral responses. In addition to coding for viral proteins, the viral genome contains signals in RNA structures that govern the amplification of viral components and participate in triggering or evading antiviral responses. In this review, we focused on new information about host-specific functions of RNA structures present in the 3' untranslated region (3' UTR) of flavivirus genomes. Models and conservation patterns of RNA elements of distinct flavivirus ecological groups are revised. An intriguing feature of the 3' UTR of insect-borne flavivirus genomes is the conservation of complex RNA structure duplications. Here, we discuss new hypotheses of how these RNA elements specialize for replication in vertebrate and invertebrate hosts, and present new ideas associating the significance of RNA structure duplication, small subgenomic flavivirus RNA formation, and host adaptation.